Personal Branding Fadil Jaidi di Media Sosial Instagram @Trafficbun.id - Handayani Hajar Aswati (Lensa, 2022)
Social media influencer named Fadil Jaidi is the CEO (Chief Executive Officer) of the food culinary business @Trafficbun.id. Fadil Jaidi not only does product branding, He also carries out a personal branding process through social media (Instagram). The purpose of the study is to determine personal branding and the steps to form Fadil Jaidi based on Instagram social media (ini kalimat indo nya gajelas jadi translate nya seadanya aja, ga ngerti maksud nya). The result of this study is that Fadil Jaidi formed a personal branding using the features on Instagram. Fadil Jaidi's personal branding process goes through 7 aspects. Specialization : Fadil Jaidi likes culinary. Leadership: he has a friendly nature (tidak melihat latar belakang kyknya masih kurang jelas deh, latar belakang apa? Tapi kalo translate nya : and does not see any kind of background). Personality: he has a humorous and humble personality. The difference/uniqueness : the clothes he used are always full color. Unity: cheerful, friendly, and humorous. Persistence: Fadil Jaidi is up to date on social media Instagram. Good intentions: never respond to haters on Instagram social media and keep uploading promos and innovations for Trafficbun.id.